A high-spin square planar iron(ii)-siloxide and its tetrahedral allogon – structural and spectroscopic models of Fe-zeolite sites. Issue 57 (5th July 2017) - Pinkert, D.; Keck, M.; Tabrizi, S. Ghassemi; Herwig, C.; Beckmann, F.; Braun-Cula, B.; Kaupp, M.; Limberg, C.
Abstract : The so far closest molecular model for the α-Fe sites in Fe-zeolites faithfully mimics the unique structure and spectroscopic features. Abstract : The famous α-Fe active sites in Fe-zeolites have recently been revealed to correspond to mononuclear high-spin iron(ii ) centres in square planar coordination environments. Here we report a first iron siloxide complex which represents a faithful structural and spectroscopic model of such sites. Notably, also an allogon with a distorted structure exists and could be crystallised.